Transition Experiences of Caregivers of Older Adults With Dementia and Multiple Chronic Conditions: An Interpretive Description Study - Annie Lam RN, MSc; Jenny Ploeg RN, PhD; Sandra L. Carroll RN, PhD; Wendy Duggleby RN, PhD; Carrie McAiney PhD; Patricia Julian RN (SAGE Publishing, 2020)
Introduction Family caregivers provide most of the care for older persons living with dementia (PLWD) and multiple chronic conditions (MCCs) in the community. Caregivers experience transitions, such as changes to their health, roles, and responsibilities, during the process of caring. Transitions encompass a time when caregivers undergo stressful responses to change. However, we know little about the transition experiences of caregivers of persons living with both dementia and MCCs. Objective This qualitative study explored the transition experiences of caregivers of PLWD within the context of MCCs, from the perspective of both caregivers and practitioners. The research question was the following: What are the transition experiences of family caregivers in providing care to older PLWD and MCCs living in the community? Methods This study was conducted using an interpretive description approach. Semistructured interviews were conducted with 19 caregivers of older community-dwelling PLWD and MCCs and 7 health-care providers working with caregivers in Ontario, Canada. Concurrent data collection and inductive data analysis were used. Results Caregivers of older PLWD and MCCs experienced four key transitions: (a) taking on responsibility for managing multiple complex conditions, (b) my health is getting worse, (c) caregiving now defines my social life, and (d) expecting that things will change. Findings highlight how the coexistence of MCCs with dementia complicates caregiver transitions and the importance of social networks for facilitating transitions. Conclusion The study provided insight on the transition experiences of caregivers of older PLWD and MCCs. MCCs increased the care load and further complicated caregivers' transition experiences. Health-care providers, such as nurses, can play important roles in supporting caregivers during these transitions and engage them as partners in care.